Looking at Happiness in Terms of Gender and Culture - Jessica Maharani, Ni Komang; Prastyadewi, Made Ika; Putri Aelia, Cresia Karenhapukh; Indah Pratiwi, I Gusti Ayu Devi; Sudarniti Ari, Ni Luh; Artari Asih, Ni Made Widya (Journal of International Conference Proceedings, 2024)
Happiness is now one of the indicators of successful development. Every country measures the happiness index of its people and competes to be the country with the happiest population. This research tries to map out happiness-related research trends in countries around the world, seeing how the results of these studies are published and making them the basis for the preparation of research related to happiness in Indonesian society. This research is a literature study with a bibliometric approach. The analysis was guided by 203 Scopus publications with the keywords “happiness,” “gender,” and “culture,” which were then narrowed down with the provisions of articles on economic subjects published between 2014-2024 and open access so that 75 articles were obtained which were then selected 5 (five) articles with the most citations. The results show that the increase in publications for the keywords “happiness,” “gender,” and “culture” continues to increase, and most publications come from the US and UK. On average, research related to happiness is more often published in psychology journals, although the content of the articles relates happiness to economic, demographic, and cultural variables.